Komunikasi Pembangunan Pariwisata Alam “Back to Nature” Pada Pengembangan Konsep Inovasi “ Glamour Camping” Ciremailand Kuningan Jawa Barat - Wulandari, Ajeng Ayu; Husnita (JIKE : Jurnal Ilmu Komunikasi Efek, 2022)
ABSTRACT Currently, tourism activities must pay attention to sustainable tourism development policies, with the concept of "back to nature" management with the aim of maintaining and preserving the tourism environment. Ciremailand glamping tourism is one of the concepts of natural tourism development with the innovation of environmental-based natural tourism development in Kuningan district, West Java. This study aims to determine the existence of decisions related to the adoption of the development of ciremail and glamping tourism innovations using qualitative methods with a constructivist type of approach where humans construct their social reality, either through giving meaning or understanding behavior actively and creatively developing responses to stimuli in their cognitive world. . The results showed that the research was in accordance with the research objectives and was said to be in accordance with the theory of the diffusion process of innovation expressed by Everett M. Rogers, namely knowledge, persuasive, implementation, decision and confirmation, that the research subjects confirmed and decided to adopt the development of tourism innovations. ciremailand glamping as a sustainable tourism development that is beneficial in maintaining the tourism environment in Kuningan Regency, West Java. Keywords: Development, Tourism, Environment, Innovation, Ciremailand